Are Indonesian Netizens Really Uncivilized? Indonesian Netizen’s Response to MSP’s Inauguration as Chairman of Brin Main Board - Pramujiono, Agung; Ardhianti, Mimas; Widya Hanindita, Amelia; Rohmah, Nur; Dian Andanty, Ferra (KnE Social Sciences, 2022)
This study examined netizens’ response to MSP’s appointment as the Chairman of Brin Main Board of the National Research and Innovation Agency (BRIN) on October 13, 2021, by President Jokowi, which caused controversy. The netizens’ responses are interesting to study from a cyber-pragmatic perspective. This study described and explained the types of netizens’ responses to the inauguration of the Chairman of Brin Main Board, the forms of netizens’ response to the inauguration, and degree of the politeness of the responses against MSP’s inauguration. The data of this study is in the form of netizens’ responses to the shows on YouTube. The data is gathered using the documentation method through the technique of Simak Bebas Libat Cakap (SBLC). The data was analysed using descriptive techniques following the stages of the interactive model of Miles and Huberman. The results of data analysis showed that there are three types of responses, namely pro responses, counter-responses, and neutral responses. The response is indicated in the form of assertive speech acts, which are stating, proposing, and informing; directive speech acts which are commanding, forbidding, advising, inviting, asking, and suggesting; and expressive speech acts, which are praising, sarcastic, and insulting. Netizens’ utterances that are not polite have a more significant percentage than polite ones. This indicates that the Indonesian netizens tend to be uncivilized in responding. Keywords: verbal response, type of response, form of response, (im)politeness, Indonesia netizens